1986
DOI: 10.1508/cytologia.51.95
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic studies on certain members of Cyperaceae from Punjab, north west India.

Abstract: The members of Cyperaceae, referred to as sedges, are common in the Punjab as nearly 36 species are known from the state flora (Nair 1978) and 25 species are recorded from Patiala itself (Sharma and Bir 1978). Inspite of a large amount of work on the cytology of sedges both in India and elsewhere, studies on the mitotic chromosomes are few and practically no work has been done on the members of north Indian plains. Therefore, the present work on karyotypes of 10 species belonging to four genera was taken up no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is a tetraploid cytotype based on x=10. Previously, the species showed chromosomal diversity with four cytotypes, n=36, 40, 42 and 44 (Bir et al 1988, Cheema et al 1993a and n= 40 (Rath and Patnaik 1975) in the studies on North Indian sedges from our laboratory.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It is a tetraploid cytotype based on x=10. Previously, the species showed chromosomal diversity with four cytotypes, n=36, 40, 42 and 44 (Bir et al 1988, Cheema et al 1993a and n= 40 (Rath and Patnaik 1975) in the studies on North Indian sedges from our laboratory.…”
Section: Resultsmentioning
confidence: 75%
“…From Southern India, Tejavathi and Nijalingappa (1990) observed mitosis of nineteen species of sedges and Subramanian (1988) worked out 18 species under six genera of Cyperaceae. Bir et al (1988Bir et al ( , 1990Bir et al ( , 1992Bir et al ( , 1996, Bir and Cheema (1994), Cheema et al (1992Cheema et al ( , 1993a, Cheema and Bir (1996), reported meiotic chromosome counts for 125 taxa under 44 species from NW India. Further Cheema et al (2017) reported meiosis in 10 species of Cyperaceae and Cheema et al (2018) worked on C. tenuispica from North India and recorded new chromosome number (2n=14).…”
mentioning
confidence: 99%
“…flavescens Roseng. (Q 3952), and then placed together in a Petri dish (96 mm) with 0.5 ml nuclear extraction buffer from (1972,1975), mehra and sachdeva (1975) 5 ii Kral (1971), rath and Patnaik (1975, 1978, Bir et al (1986Bir et al ( , 1988Bir et al ( , 1990Bir et al ( , 1992 Kral (1971) the kit Partec CyStain PI Absolute P (05-5022). Samples were ground with a razor blade.…”
Section: Materials Studiedmentioning
confidence: 99%
“…Cytologists have examined grasses from different parts of India: eastern (Sharma and Sharma, 1961;Sharma and Chatterjee, 1967;Sanyal and Sharma, 1972a,b;Mehra and Sachdeva, 1975;Mehra, 1982), northeastern (Mehra and Chaudhary, 1981;Kalia and Mehra, 1986;Christopher and Jacob, 1990), central (Koul and Paliwal, 1964;Gill et al, 1980), southern (Venkateswarlu and Pantulu, 1970;Christopher and Abraham, 1971;Christopher et al, 1987;Nijalingappa and Bai, 1990;Rao et al, 1993;Nair et al, 1999;Kameshwari and Muniyamma, 2001) and northern (Mehra and Kohli, 1966;Sharma and Kaur, 1980;Sharma and Kumar, 1985;Bir et al, 1987;Gupta et al, 2008;Gupta and Gupta, 2008). For northwest India -Punjab along with part of Haryana covered in the last decade - Bir et al (1986Bir et al ( , 1990, Cheema and Bir (1995), Gupta and Gupta (2008), Gupta et al (2008), Gupta (2009) and Kaur andGupta (2008-2009) have made significant studies of members of the Cyperaceae and Poaceae families. For the Western Himalayas a large number of cytological reports are available for monocots from Kashmir (Mehra and Remanandan, 1973;Mehra and Sharma, 1977;Mehra and Pandita, 1984;Pandita and Mehra, 1984;Pandita, 1986;Gohil and Koul, 1988;Koul and Gohil, 1989, 1991.…”
Section: Frequency Of Cytologically Known Taxamentioning
confidence: 99%